PHYSICAL-MECHANICAL PROPERTIES AND HEAT TRANSFER ANALYSIS OF OSB PRODUCED WITH PHENOL-FORMALDEHYDE AND ZnO NANOPARTICLES ADDITION - Silva, Maria Fernanda Felippe [UNESP]; Silva, Joao Vitor Felippe [UNESP]; Favarim, Higor Rogerio [UNESP]; Campos, Cristiane Inacio de [UNESP] (Univ Bio-bio, 2023)
Oriented Strand Board is a structural wood composite with applications that require good physical and mechanical performance. The addition of ZnO nanoparticles is an alternative that has been studied in order to improve the properties of Oriented Strand Board panels. However, there is no information about its effect Oriented Strand Board. The aim of this work was to evaluate the influence of the addition of zinc oxide nanoparticles in two different percentages (0,25 % and 0,50 %) on the physical-mechanical properties of Oriented Strand Board panels produced with phenol-formaldehyde resin and on the heat transfer during hot-pressing. Oriented Strand Board panels were produced and tested according to European Standards. The addition of ZnO nanoparticles improved the dimensional stability of the panel, reducing its thickness swelling, and also increased the screw withdraw strength. The heat transfer during hot-pressing increased the tempera-ture more quickly on boards with nanoparticles addition; on the other hand the final temperature of the control treatment was higher.
Keywords: Material properties; Oriented Strand Board; Pinus elliottii; wood composite; zinc oxide